2009
DOI: 10.1667/rr1238.1
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Rate Effectiveness for Unstable-Type Chromosome Aberrations Detected in Mice after Continuous Irradiation with Low-Dose-Rate γ Rays

Abstract: Chronological changes in the chromosome aberration rates of splenocytes from specific-pathogen-free (SPF) mice after continuous and long-term exposure to low-dose-rate gamma rays were studied. Incidences of dicentrics plus centric rings (Dic+Rc), detected by conventional Giemsa staining, and dicentric chromosomes, detected by fluorescence in situ hybridization (Dic by FISH) using a centromere probe, showed an essentially linear increase up to a total accumulated dose of 8000 mGy after irradiation for about 400… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
29
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 22 publications
7
29
0
Order By: Relevance
“…As shown earlier in TERT-immortalized human fibroblast, the cytogenetic lesions frequency as well as an elimination of cells irradiated at a low dose rate (0.3 mGy/min) were significantly lower than those in cells irradiated at a high dose rate (2000 mGy/min) [21]. Similar effects were observed in the animal model experiments [2224]. …”
Section: Resultssupporting
confidence: 79%
“…As shown earlier in TERT-immortalized human fibroblast, the cytogenetic lesions frequency as well as an elimination of cells irradiated at a low dose rate (0.3 mGy/min) were significantly lower than those in cells irradiated at a high dose rate (2000 mGy/min) [21]. Similar effects were observed in the animal model experiments [2224]. …”
Section: Resultssupporting
confidence: 79%
“…XXXX, XXX, XXX−XXX even in mice captured in this heavily contaminated area, the frequency of chromosomal aberrations might have increased to a large extent. Thus, our results showing a 2-to 3-fold increase in the frequency of dicentric chromosomes in mice captured in the moderately and heavily contaminated areas (Figure 2) is consistent with the data of laboratory mice reported by Tanaka et al 23 Potential Variation in Cell-Cycling of Splenic Lymphocytes of Wild Mice. Chromosomal aberrations induced in vivo as a biomarker of the effect of radiation should preferentially be observed in M1 metaphase cells after the cells are forced to enter the cell cycle in vitro, since over multiple cell cycle progressions, unstable chromosomal aberrations formed in vivo might dilute out or disappear, while additional, derivative aberrations might appear due to in vitro culturing conditions.…”
Section: Environmental Science and Technologysupporting
confidence: 93%
“…reported that, with a low-dose-rate of 0.02 Gy/day, the number of dicentric chromosome in spleen cells increases almost linearly as the total accumulated IR dose increased up to the highest dose of 8 Gy; however, such an increase is not evident with a dose-rate of 0.001 Gy/day [25]. Although the dose-rate was not similar to our study, we are able to assume that mis-joining of DSBs on two different chromosome might have spatial as well as temporal limitations, and this is the reason why accumulation of dicentric chromosome was not observed following fractionated irradiation with prolonged fraction intervals with 5 minutes or more.…”
Section: Discussionmentioning
confidence: 99%